Ultra-small nano low-valence copper negative pressure drainage sponge and preparation method thereof
By using medical negative pressure drainage sponges prepared with ultra-small nano low-priced copper particles and other materials, the existing sponges have poor antibacterial properties and slow wound healing speed have been solved, and the effect of efficiently reducing reactive oxygen concentration and promoting wound healing is achieved.
Patent Information
- Application Number
- CN202411787440.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing medical negative pressure drainage sponges are hydrophilic and water-retaining, but have poor antibacterial properties and slow wound healing speed.
The sponge matrix is prepared by ultra-small nano-low-price copper particles, polyester polyol, hexamethylene diisocyanate and sodium alginate, and an anti-adhesion layer is applied to the sponge matrix. The enzyme catalytic properties and antioxidant activity of ultra-small nano-low-price copper particles are used to reduce the reactive oxygen concentration and enhance antibacterial properties.
Effectively reduce the concentration of reactive oxygen species, improve antibacterial properties, promote wound healing, and prevent granulation from growing.
Smart Images

Figure CN119564915A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to an ultra-small nano low-cost copper negative pressure drainage sponge and a preparation method thereof. Background Art
[0002] Skin trauma is a global health problem, and effectively rebuilding the function and integrity of damaged tissues is the focus of current clinical treatment. The ideal condition for skin wound healing is in a humid environment. At the same time, the body consumes carbohydrates to provide energy during wound healing, but this process also produces a large amount of reactive oxygen species (ROS), which plays an important role in affecting the speed of wound healing. Generally, low concentrations of reactive oxygen species promote wound healing, while high concentrations of reactive oxygen species inhibit wound healing. An ideal sponge should have the following characteristics: good hydrophilicity, water retention, antibacterial ability, ability to promote wound healing, ability to prevent granulation growth, etc.
[0003] Although traditional polyurethane medical negative pressure drainage sponges have solved the hydrophilic and water retention properties, effectively dealt with the problem of storing wound exudate, and created a relatively good humid environment, the humid environment also provides attachment points for foreign bacteria, and at the same time fails to solve the problem of how to reduce the concentration of active oxygen to promote wound healing. Therefore, the design of a medical negative pressure drainage sponge is an urgent problem to be solved in this field, and it also has broad prospects. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide an ultra-small nano low-cost copper negative pressure drainage sponge and a preparation method thereof, and solve the technical problems in the prior art that the negative pressure drainage sponge is hydrophilic and water-retaining but has poor antibacterial properties and slow wound healing speed.
[0005] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides an ultra-small nano low-valent copper negative pressure drainage sponge, comprising a sponge matrix, and / or, also comprising an anti-sticking layer arranged on the sponge matrix; the raw materials of the sponge matrix include, by weight: 8 to 12 parts of polyester polyol, 0.1 to 0.2 parts of ultra-small nano low-valent copper particles, 0.2 to 0.4 parts of foaming agent, 0.2 to 0.3 parts of silicon surfactant, 0.3 to 0.4 parts of catalyst, 1.5 to 2.5 parts of sodium alginate and 12 to 18 parts of hexamethylene diisocyanate; the ultra-small nano low-valent copper particles are prepared from copper salt and phenolic reducing agent as raw materials, and contain Cu2O and CuO.
[0006] In a second aspect, the present invention provides a method for preparing an ultrasmall nano low-valent copper negative pressure drainage sponge, comprising the following steps: S1, preparing ultrasmall nano low-valent copper particles using copper salt and phenolic reducing agent as raw materials; S2, uniformly mixing polyester polyol, ultrasmall nano low-valent copper particles, foaming agent, silicon surfactant, catalyst, sodium alginate and hexamethylene diisocyanate to obtain a mixture; foaming and curing the mixture to obtain a sponge matrix; and / or, S3, coating an anti-sticking layer on the sponge matrix to obtain an ultrasmall nano low-valent copper negative pressure drainage sponge.
[0007] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses ultra-small nanometer low-valent copper particles, polyester polyol, hexamethylene diisocyanate and sodium alginate as raw materials, mixes them and foams and solidifies them to obtain a sponge matrix, wherein the ultra-small nanometer low-valent copper particles contain Cu2O and CuO, have enzyme catalytic performance and antioxidant activity, and have antibacterial properties; sodium alginate is used to effectively improve the hydrophilicity of the negative pressure drainage sponge; therefore, the negative pressure drainage sponge of the present invention can reduce the concentration of active oxygen, has good antibacterial properties (the antibacterial rate is above 90%), and effectively promotes wound repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is the XPS peak diagram of the ultra-small nano low-cost copper particles obtained by the present invention. DETAILED DESCRIPTION
[0009] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0010] Although the traditional polyurethane medical negative pressure drainage sponge has good hydrophilicity and water retention, effectively solves the problem of storing wound exudate and creates a relatively good humid environment, the humid environment also provides attachment points for foreign bacteria, and fails to solve the problem of how to reduce the concentration of active oxygen to promote the wound healing speed. Based on this, the present invention is established.
[0011] In a first aspect, the present invention provides an ultra-small nano low-valent copper negative pressure drainage sponge, comprising a sponge matrix, and / or, also comprising an anti-sticking layer arranged on the sponge matrix; the raw materials of the sponge matrix include, by weight: 8 to 12 parts of polyester polyol, 0.1 to 0.2 parts of ultra-small nano low-valent copper particles, 0.2 to 0.4 parts of foaming agent, 0.2 to 0.3 parts of silicon surfactant, 0.3 to 0.4 parts of catalyst, 1.5 to 2.5 parts of sodium alginate and 12 to 18 parts of hexamethylene diisocyanate; the ultra-small nano low-valent copper particles are prepared from copper salt and phenolic reducing agent as raw materials, and contain Cu2O and CuO.
[0012] Copper (Cu) is an essential trace element for the human body and plays an important role in various enzymes such as tyrosinase. Therefore, copper-based nanomaterials can be used to remove ROS; and cuprous oxide (Cu2O) has good catalytic activity, can promote electron transfer reaction, thereby partially simulating peroxidase. Therefore, the present invention can simultaneously obtain enzyme catalytic performance and antioxidant activity by combining Cu2O and CuO nanoparticles. At the same time, as a low-valent copper, it will enter the interior of bacterial cells through charge attraction, destroy its cell wall and internal protein enzymes, thereby having antibacterial and anti-inflammatory effects. The ultra-small nano low-valent copper particles are foamed with polyester polyols, hexamethylene diisocyanate and sodium alginate to obtain a sponge matrix, and then an anti-sticking layer is coated on the sponge matrix to effectively achieve a series of purposes such as reducing the concentration of active oxygen, preventing external bacterial invasion, absorbing tissue exudate, preventing wound adhesion and preventing granulation from growing in.
[0013] Preferably, the ultra-small nano low-valent copper particles contain Cu2O and CuO in a molar ratio of 1: (6-8). The low-valent copper mixture at this ratio has relatively good performance, which is beneficial to improving the enzyme catalytic performance and antioxidant activity, thereby achieving the most favorable environment for wound recovery.
[0014] Preferably, the mass ratio of polyester polyol to ultra-small nano low-valent copper particles is 10:(0.1-0.2).
[0015] Preferably, the molar ratio of the total hydroxyl value of the polyester polyol to the total isocyanate value of hexamethylene diisocyanate is 1:(1.1-1.2).
[0016] Preferably, the foaming agent includes deionized water; the silicon surfactant includes a silane coupling agent; and the catalyst includes stannous octoate.
[0017] Preferably, the material of the anti-sticking layer includes polydimethylsiloxane; the thickness of the negative pressure drainage sponge is 24 to 32 mm, and the thickness of the anti-sticking layer is 1.5 to 6.5 mm.
[0018] In a second aspect, the present invention provides a method for preparing an ultra-small nano low-cost copper negative pressure drainage sponge, comprising the following steps: S1, preparing ultra-small nano low-valent copper particles using copper salt and phenolic reducing agent as raw materials; S2, mixing polyester polyol, ultra-small nano low-cost copper particles, foaming agent, silicon surfactant, catalyst, sodium alginate and hexamethylene diisocyanate uniformly to obtain a mixture; foaming and curing the mixture to obtain a sponge matrix; and / or, S3, coating an anti-sticking layer on the sponge substrate to obtain an ultra-small nano low-cost copper negative pressure drainage sponge.
[0019] Preferably, in step S1, preparing ultra-small nano low-valent copper particles specifically includes: adding copper salt and phenolic reducing agent to deionized water, reacting at 75-95°C for 12-18h, cooling to room temperature after the reaction is completed and standing for stratification, taking the supernatant and centrifuging, dialyzing and drying to obtain ultra-small nano low-valent copper particles. In the specific reaction temperature and time conditions of copper salt and phenolic reducing agent, when it is lower than 75°C, the reduction reaction cannot be induced due to the low temperature. When it is higher than 95°C, a large number of nano-copper clusters will be agglomerated, and dissolved oxygen will be reduced. For the control of reaction time, the overall reaction time is greater than 12h. A shorter reaction time will result in incomplete reaction of tea polyphenols and copper chloride, and the overall reaction tends to be stable after 12h.
[0020] Further preferably, the copper salt includes copper chloride, the phenolic reducing agent includes tea polyphenols, the mass ratio of the copper salt to the phenolic reducing agent is 1: (2.4-2.6), and the mass ratio of the copper salt to deionized water is (4-6): 100. When the amount of the phenolic reducing agent such as tea polyphenols is too small, the antioxidant capacity of the obtained nano-copper clusters will be insufficient, and when the proportion of tea polyphenols is too high, the content of Cu2O in the obtained nano-copper clusters will be too low, and the enzyme-like effect will be lost.
[0021] More preferably, tea polyphenols can be added to deionized water using green tea or other phenol-rich reducing substances, and rapidly stirred for 2 to 3 hours at 120 to 130°C; after cooling to room temperature, the liquid phase is dried to obtain phenolic substances in green tea. The tea polyphenols or phenolic substances in tea leaves used as raw materials in the present invention are all edible substances. The green preparation method improves the safety of the present invention and can provide a new idea for the development of medical negative pressure drainage sponges.
[0022] Further preferably, the centrifugal conditions include: a rotation speed of 3000-5000 r / min, a time of 20-30 min; and a dialysis bag with a molecular weight cutoff of 8000-10000 Da is used during dialysis. Among them, the molecular weight cutoff (Mw cutoff) of the dialysis bag used is preferably 10000 Da, which can control the size of copper to be below 5 nm. A smaller size is conducive to metabolism through the kidneys after being absorbed by the human body.
[0023] Preferably, in step S2, the polyester polyol is firstly mixed evenly with the ultra-small nano low-valent copper particles, and then the foaming agent, the silicon surfactant, the catalyst and the sodium alginate are added, and stirred at a speed of 800 to 1200 r / min for 10 to 20 s, and finally hexamethylene diisocyanate is added, and stirred at a speed of 1000 to 1500 r / min for 15 to 25 s to obtain a mixture.
[0024] Preferably, in step S2, the foaming conditions are: stirring and foaming with a stirring rod at room temperature, the stirring time is 20 to 30 seconds, and the speed is 600 to 1200 r / min; the curing temperature is 55 to 65° C., and the curing time is 18 to 24 hours.
[0025] The present invention is further described in detail below through specific examples.
[0026] Example 1 A method for preparing an ultra-small nano low-cost copper negative pressure drainage sponge comprises the following steps: S1, preparation of ultra-small nano-low-cost copper particles: 5 g of copper chloride was dissolved in 100 mL of deionized water, 12 g of tea polyphenols was added, and the mixture was reacted at 85°C for 12 h. After the reaction was completed, the mixture was cooled for 6 h, and the mixed solution was cooled to room temperature and separated into layers. The supernatant was centrifuged at 4000 r / min for 25 min and the supernatant was collected again. The supernatant was dialyzed using a dialysis bag (molecular weight cutoff: 10000 Da) for 48 h to obtain the final solution. The final solution was freeze-dried for 48 h to obtain ultrasmall nano low-valent copper particles.
[0027] The obtained ultra-small nano-low-cost copper particles were measured by XPS, and the peak fitting was performed by the software Avantage, and the peak diagram was obtained as follows: Figure 1 As shown. Figure 1 It can be seen that the ultra-small nano low-valent copper particles prepared in the present invention contain Cu2O and CuO, and the peak area ratio of the two is 1:7.7, that is, the molar ratio of Cu2O to CuO is 1:7.7.
[0028] S2, preparation of medical polyurethane negative pressure drainage sponge matrix: After 10g of polyester polyol (YSH908) and 0.1g of ultra-small nano low-cost copper particles were mixed evenly, 0.4g of water, 0.3g of silane coupling agent KH-561, 0.4g of stannous octoate, and 2g of sodium alginate were added and stirred at 1000r / min for 15s at room temperature; after adding 15g of hexamethylene diisocyanate, the mixture was stirred at 1200r / min for 20s, and then quickly poured into a mold for foaming. The prepared foam was placed in an oven and cured at 60°C for 20h to obtain a sponge matrix.
[0029] S3, preparing anti-sticking layer: The inner layer of the sponge matrix (the side to be in contact with the wound) after curing was coated with polydimethylsiloxane (thickness of 2 mm), and then dried again for 12 hours to obtain a negative pressure drainage sponge.
[0030] Example 2 The only difference from Example 1 is that step S2 is different, and step S1 and step S3 are the same as those of Example 1; the difference is that: S2, after 10g polyester polyol (YSH908) and 0.15g ultra-small nano low-cost copper particles are mixed evenly, 0.2g water, 0.2g silane coupling agent KH-561, 0.3g stannous octoate, and 2g sodium alginate are added, and stirred at 1000r / min for 15s at room temperature; after adding 15g hexamethylene diisocyanate, stir at 1200r / min for 20s, and then quickly pour into the mold for foaming. The prepared foam is placed in an oven and cured at 60°C for 20h to obtain a sponge matrix.
[0031] Example 3 The only difference from Example 2 is that the amount of ultra-small nano low-cost copper particles in step S2 is adjusted to 0.2 g, and the other steps and conditions are the same as those in Example 2.
[0032] Example 4 (without anti-adhesive layer) S1, preparation of ultra-small nano-low-cost copper particles: 5 g of copper chloride was dissolved in 100 ml of deionized water, 12 g of tea polyphenols was added, and the mixture was reacted at 85°C for 12 hours. After the reaction was completed, the mixture was cooled for 6 hours, and the mixed solution was cooled to room temperature and separated into layers. The supernatant was centrifuged at 4000 r / min for 25 minutes and the supernatant was collected again. The supernatant was dialyzed for 48 hours using a dialysis bag (molecular weight cutoff Mw cutoff: 10000Da) to obtain the final solution. The final solution was freeze-dried for 48 hours to obtain ultra-small nano low-valent copper particles.
[0033] S2, preparation of medical polyurethane negative pressure drainage sponge: After 10g of polyester polyol (YSH908) and 0.1g of ultra-small nano low-cost copper particles are mixed evenly, 0.4g of water, 0.2g of silane coupling agent KH-561, 0.3g of stannous octoate, and 2g of sodium alginate are added and stirred at 1000r / min for 15s at room temperature; 15g of hexamethylene diisocyanate (the molar ratio of the total hydroxyl value of polyester polyol and the isocyanate group in hexamethylene diisocyanate is 1:1.1) is added and stirred at 1200r / min for 20s, and then quickly poured into a mold for foaming. The prepared foam is placed in an oven for curing to obtain a medical sponge.
[0034] Comparative Example 1 (non-hydrophilic control group) The only difference from Example 1 is that sodium alginate is removed in step S2, and the other steps and conditions are the same as those in Example 1.
[0035] Comparative Example 3 (low copper content control group) The only difference from Example 2 is that the amount of ultra-small nano low-cost copper particles in step S2 is adjusted to 0.02 g, and the other steps and conditions are the same as those in Example 2.
[0036] Comparative Example 4 (low copper content control group) The only difference from Example 2 is that the amount of ultra-small nano low-cost copper particles in step S2 is adjusted to 0.08 g, and the other steps and conditions are the same as those in Example 2.
[0037] Performance Testing Hydrophilicity: The contact angle test of the anti-adhesive layer of the obtained negative pressure drainage sponge was carried out using a contact angle measuring instrument Dataphysics DCAT21.
[0038] Antibacterial performance: Using the oscillation method, the dry negative pressure drainage sponge sample was added to the liquid culture medium to swell to swelling equilibrium, then transferred to 50 mL of fresh beef peptone liquid culture medium, inoculated with bacterial solution, and cultured at 37°C for 24 h. The experimental group (bacterial solution concentration was 10 6 The inhibitory rate was calculated by comparing the absorbance of the sample group (absorbance of 0.1447 W / mL) and the absorbance of the blank group (bacterial solution without sample) / absorbance of the blank group × 100%. The test results are shown in Table 1.
[0039] ROS scavenging ability test: The DPPH antioxidant test was used to evaluate the antioxidant capacity (ROS scavenging ability) of the negative pressure drainage sponge sample of the present invention. First, 4 mg of DPPH was dispersed in 100 ml of methanol. Then, 3 mL of DPPH solution was taken and added to the same volume of sample solution containing different amounts (0, 300, 500, 1000 μg / mL). Finally, the reaction solution was taken out at 120 min, and the absorbance value of the mixed solution at 516 nm was detected, and the clearance rate was calculated, and the formula was [1-(A i -A j ) / A c ],in: A i : absorbance of DPPH solution at 516 nm; A j : Absorbance of sample solution + DPPH solution at 516 nm; A c : Absorbance of sample solution at 516nm.
[0040] Anti-skin adhesion performance: A mouse wound model was designed. The back of the mouse was taken. Under general anesthesia, a full-thickness wound (d = 5 mm) was taken on the outside of the spine of each mouse with a sterile scalpel. Then the negative pressure drainage sponge of the present invention was used on the surface of the wound (the anti-adhesion layer directly contacts the wound), and skin adhesion was observed after 3 days. All animal experiments were approved by the Animal Care and Use Committee of Wuhan University of Technology, and the animal experiment ethics approval number is WHUT (2022-042). Among them, the criterion for skin adhesion is whether there is granulation growth between the dressing and the skin to form an integrated structure.
[0041] Wound healing rate: A mouse wound model was designed. The back of the mouse was taken. Under general anesthesia, a full-thickness wound (d = 10 mm) was made on the outside of the spine of each mouse using a sterile scalpel. Then the negative pressure drainage sponge of the present invention was used on the wound surface (the anti-adhesive layer directly contacts the wound surface), and the healing condition was observed after 14 days. Among them, the healing standard: a circular wound with d = 10 mm was set on the first day, and the wound recovery was observed after 14 days. In the wound area, if the wound has been aligned neatly, there is no redness, swelling, or exudate, it means that the wound has healed.
[0042] The negative pressure drainage sponge samples prepared in each embodiment and comparative example were tested by the above method, and the test results are shown in Table 1 below.
[0043] Table 1 Performance test results of various embodiments and comparative examples
[0044] As can be seen from Table 1, except for Comparative Example 1, the water droplets dripped on the negative pressure drainage sponge samples obtained in other embodiments and comparative examples were quickly and completely absorbed into the sponge matrix, indicating good wettability, so the water contact angles were all recorded as 0°, while the water droplets on the sample of Comparative Example 1 could not be quickly absorbed, and the actual contact angle could be measured to be 116°, proving that by adding sodium alginate, the hydrophilic effect of the negative pressure drainage sponge obtained by the present invention is good.
[0045] In Example 4, there was a slight adhesion between the back wound of the mouse and the negative pressure drainage sponge, but the wound was able to heal within the same time; and compared with Example 1, the biggest difference in Example 4 was that the anti-sticking layer was removed (the amount of silane coupling agent and stannous octoate used was very small, and its effect was negligible), and its antibacterial rate and free radical scavenging rate were also slightly reduced, which showed that setting up an anti-sticking layer was more beneficial to the antibacterial rate and promoting wound healing.
[0046] The content of low-valent copper was increased proportionally in Comparative Example 2-3 and Example 2-3. In Comparative Example 2-3, the wound on the back of the mouse had not healed, and a small number of colonies appeared in the antibacterial test, while the wound in Example 2-3 had healed. It can be concluded that the ultrasmall nano low-valent copper particles in the negative pressure drainage sponge of the present invention have an effect of promoting wound healing, and the concentration will affect the promoting effect. It also has good antibacterial effect and free radical scavenging effect.
[0047] Therefore, the negative pressure drainage sponge prepared by the present invention effectively solves a series of problems such as storing wound tissue fluid, reducing active oxygen concentration, preventing external bacteria from infiltrating, and preventing adhesion to the wound. The ultra-small nano low-valent copper prepared from tea polyphenols or phenols in tea leaves and copper chloride can effectively remove active oxygen at extremely low concentrations and have an antibacterial effect. At the same time, the tea polyphenols and phenol extracts in tea leaves as reducing agents are edible, which improves the clinical safety performance of the medical negative pressure drainage sponge. The invention can provide a new idea for the development of medical negative pressure drainage sponges.
[0048] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. An ultra-small nano low-cost copper negative pressure drainage sponge, characterized in that: It comprises a sponge matrix, and / or, further comprises an anti-sticking layer arranged on the sponge matrix; The raw materials of the sponge matrix include, by weight: 8 to 12 parts of polyester polyol, 0.1 to 0.2 parts of ultra-small nano low-cost copper particles, 0.2 to 0.4 parts of foaming agent, 0.2 to 0.3 parts of silicon surfactant, 0.3 to 0.4 parts of catalyst, 1.5 to 2.5 parts of sodium alginate and 12 to 18 parts of hexamethylene diisocyanate; The ultra-small nanometer low-valent copper particles are prepared using copper salt and phenolic reducing agent as raw materials, and contain Cu2O and CuO.
2. The ultra-small nano low-cost copper negative pressure drainage sponge according to claim 1, characterized in that: The ultra-small nano low-valent copper particles contain Cu2O and CuO in a molar ratio of 1: (6-8).
3. The ultra-small nano low-cost copper negative pressure drainage sponge according to claim 1, characterized in that: The mass ratio of the polyester polyol to the ultra-small nano low-valent copper particles is 10: (0.1-0.2); The ratio of the polyester polyol to the hexamethylene diisocyanate is 1:(1.1-1.2).
4. The ultra-small nano low-cost copper negative pressure drainage sponge according to claim 1, characterized in that: The foaming agent includes deionized water; The silicon surfactant includes a silane coupling agent; The catalyst includes stannous octoate.
5. The ultra-small nano low-cost copper negative pressure drainage sponge according to claim 1, characterized in that: The raw material of the anti-sticking layer includes polydimethylsiloxane; The thickness of the negative pressure drainage sponge is 24-32 mm, and the thickness of the anti-adhesion layer is 1.5-6.5 mm.
6. The method for preparing the ultra-small nano low-cost copper negative pressure drainage sponge according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, preparing ultra-small nano low-valent copper particles using copper salt and phenolic reducing agent as raw materials; S2, mixing polyester polyol, ultra-small nano low-cost copper particles, foaming agent, silicon surfactant, catalyst, sodium alginate and hexamethylene diisocyanate uniformly to obtain a mixture; foaming and curing the mixture to obtain a sponge matrix; and / or, S3, coating an anti-sticking layer on the sponge substrate to obtain an ultra-small nano low-cost copper negative pressure drainage sponge.
7. The method for preparing the ultra-small nano low-cost copper negative pressure drainage sponge according to claim 6, characterized in that: In step S1, preparing ultrasmall nano low-valent copper particles specifically includes: adding copper salt and phenolic reducing agent into deionized water, reacting at 75-95°C for 12-18h, cooling to room temperature after the reaction is completed and standing to separate layers, taking the supernatant and subjecting it to centrifugation, dialysis and drying to obtain ultrasmall nano low-valent copper particles.
8. The method for preparing the ultra-small nano low-cost copper negative pressure drainage sponge according to claim 7, characterized in that: The copper salt includes copper chloride, and the phenolic reducing agent includes tea polyphenols; the mass ratio of the copper salt to the phenolic reducing agent is 1:(2.4-2.6); the mass ratio of the copper salt to deionized water is (4-6):100; The centrifugal conditions include: a rotation speed of 3000 to 5000 r / min and a time of 20 to 30 min; The dialysis uses a dialysis bag with a molecular weight cut-off of 8000 to 10000 Da.
9. The method for preparing the ultra-small nano low-cost copper negative pressure drainage sponge according to claim 6, characterized in that: In step S2, the polyester polyol is firstly mixed evenly with the ultra-small nano low-cost copper particles, and then the foaming agent, the silicon surfactant, the catalyst and the sodium alginate are added, and stirred at a speed of 800 to 1200 r / min for 10 to 20 seconds, and finally hexamethylene diisocyanate is added, and stirred at a speed of 1000 to 1500 r / min for 15 to 25 seconds to obtain a mixture.
10. The method for preparing the ultra-small nano low-cost copper negative pressure drainage sponge according to claim 6, characterized in that: In step S2, the foaming conditions are: stirring at a rotation speed of 600 to 1200 r / min for 20 to 30 seconds; the curing temperature is 55 to 65° C., and the curing time is 18 to 24 hours.
Citation Information
Patent Citations
Preparation method of immobilized Cu2O / Cu@ACSs photocatalyst as well as preparation method and application thereof
CN110180543A
Nano-antibacterial sponge with strong water absorption and preparation method thereof
CN113292694A
Hydrophilic polyurethane dressing and preparation method thereof
CN113713163A
Antistatic antibacterial biaxially oriented polyester composite film and preparation method thereof
CN116655983A
Metal polyphenol-based nano-particles, preparation method thereof and application of metal polyphenol-based nano-particles in treatment of acute kidney injury
CN116870029A